Microbial Profile of Salted Parrotfish (Bajo) in Tanjung Luar Traditional Market - Jannah, Mirriyadhil; Suwasono, Sony; Nalurita, Indah (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Salted parrotfish (Bajo) from East Lombok is a traditional product vulnerable to microbial contamination. This study aimed to identify microbiological hazards in Bajo salted fish marketed at Tanjung Luar Market. Ten samples were analyzed using Total Plate Count (TPC), yeast and mold enumeration, the Most Probable Number (MPN) method for coliforms and Escherichia coli, and selective isolation for Salmonella sp., Vibrio sp., and Staphylococcus aureus. TPC values ranged from 8.2 × 10⁴ to 1.5 × 10⁵ CFU/g, with several samples exceeding the SNI 2721:2009 limit (1 × 10⁵ CFU/g). Yeast and mold counts (1.2 × 10² – 6.8 × 10⁴ CFU/g) remained below the BPOM threshold. All samples contained coliforms (15–46 MPN/g), and most were positive for E. coli (up to 15 MPN/g), surpassing the SNI limit (<3 MPN/g). Salmonella sp. was not detected, whereas Vibrio sp. was found in three producers. Staphylococcus aureus was present in all samples (1.3 × 10² – 2.5 × 10² CFU/g), though still below the permitted limit (1 × 10³ CFU/g). These results indicate that Bajo salted fish remains contaminated with hygiene indicator bacteria and pathogenic microorganisms, particularly E. coli and Vibrio sp., posing potential health risks. Strengthened hygiene and sanitation practices in processing, storage, and distribution are essential to ensure product safety.